Studies on the acid phosphatase activity of the diamondback moth, Plutella xylostella (L) (Lepidoptera: Plutellidae) - Sofian-Azirun, M. (Malaysian Journal of Science, 1994)
Studies on the activity of acid phosphatasein Plutella xylostella were carried out using p-nitrophenyl phosphate as the substrate. The optimum pH was between 4.75 to 5 and enhancement in phosphatase activity was apparent up to 450C . Attempts were made to study the effects of malathion, malaoxon, dichlorvos and p- and hydroxymercuribenzoateon theacidphosphatase activity. Click for full abstract.